Age Drives Distortion of Brain Metabolic, Vascular and Cognitive Functions, and the Gut Microbiome - Hoffman, Jared D.; Parikh, Ishita; Green, Stefan J.; Chlipala, George; Mohney, Robert P.; Keaton, Mignon; Bauer, Bjoern; Hartz, Anika M. S.; Lin, Ai-Ling (Frontiers in Aging Neuroscience, 2017)
Advancing age is the top risk factor for the development of neurodegenerative disorders, including Alzheimer’s disease (AD). However, the contribution of aging processes to AD etiology remains unclear. Emerging evidence shows that reduced brain metabolic and vascular functions occur decades before the onset of cognitive impairments, and these reductions are highly associated with low-grade, chronic inflammation developed in the brain over time. Interestingly, recent findings suggest that the gut microbiota may also play a critical role in modulating immune responses in the brain via the brain-gut axis. In this study, our goal was to identify associations between deleterious changes in brain metabolism, cerebral blood flow, gut microbiome, and cognition in aging, and potential implications for AD development. We conducted our study with a group of young mice (5-6 months of age) and compared those to old mice (18-20 months of age) by utilizing metabolic profiling, neuroimaging, gut microbiome analysis, behavioral assessments, and biochemical assays. We found that compared to young mice, old mice had significantly increased levels of numerous amino acids and fatty acids that are highly associated with inflammation and AD biomarkers. In the gut microbiome analyses, we found that old mice had increased Firmicutes/Bacteroidetes ratio and alpha diversity. We also found impaired blood-brain barrier function and reduced cerebral blood flow as well as compromised learning and memory and increased anxiety, clinical symptoms often seen in AD patients, in old mice. Our study suggests that the aging process involves deleterious changes in brain metabolic, vascular and cognitive functions, and gut microbiome structure and diversity, all which may lead to inflammation and thus increase the risk for AD. Future studies conducting comprehensive and integrative characterization of brain aging, including crosstalk with peripheral systems and factors, will be necessary to define the mechanisms underlying the shift from normal aging to pathological processes in the etiology of AD.